2020
DOI: 10.1002/csc2.20097
|View full text |Cite
|
Sign up to set email alerts
|

Associations between first true leaf physiology and seedling vigor in cotton under different field conditions

Abstract: Rapid development of the first true leaf has been suggested as a key driver of seedling vigor in cotton, yet studies demonstrating an association between first true leaf physiological processes and early season cotton growth are limited. It was hypothesized that both first true leaf area (FTLA) and photosynthetic rates would be positively associated with cotton (Gossypium hirsutum and G. barbadense) seedling vigor, and that photosynthetic component processes would differ in their contribution to net photosynth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Small-plot studies conducted in Georgia also showed that largerseeded cultivars tended to have greater seedling vigor, especially when planted early in the season under sub-optimal temperature conditions (Virk et al, 2019(Virk et al, , 2020b. Other than cultivar, seed physical and chemical traits are also governed by environmental conditions (temperature, humidity) during seed development and storage.…”
mentioning
confidence: 99%
“…Small-plot studies conducted in Georgia also showed that largerseeded cultivars tended to have greater seedling vigor, especially when planted early in the season under sub-optimal temperature conditions (Virk et al, 2019(Virk et al, , 2020b. Other than cultivar, seed physical and chemical traits are also governed by environmental conditions (temperature, humidity) during seed development and storage.…”
mentioning
confidence: 99%
“…Extensive research has been conducted on the factors affecting seedling vigour in cotton, and it is clear that cultivar and growth temperature are among the most important determinants of early‐season growth [Liu et al., 2015; Snider et al., 2014; Snider et al., 2016; Snider et al., 2018; Virk et al., 2019, 2020]. However, other than a few recently published works [Liu et al., 2019; St Aime et al., 2021; Singh et al., 2018], studies that have evaluated vigour as a function of root system development are limited.…”
Section: Discussionmentioning
confidence: 99%
“…vigour can be affected by cotton cultivar [Snider et al, 2014;Snider et al, 2016;Virk et al, 2019;Virk et al, 2020] and environmental constraints such as suboptimal temperatures that occur at or soon after planting (Snider et al, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows weather conditions prevailing during seven day period proceeding the date of physiological measurements. Chlorophyll fluorescence assessments were also conducted at the same time using the methods and calculations discussed extensively elsewhere (Earl and Ennahli, 2004;Chastain et al, 2016;Meeks et al, 2019;Virk et al, 2020b). The primary fluorescence parameters of interest included actual quantum yield of photosystem II (Φ PSII ) and rate of electron flux through photosystem II (ETR).…”
Section: Gas Exchange and Chlorophyll Fluorescence Measurementsmentioning
confidence: 99%